1985
DOI: 10.1161/01.str.16.2.323
|View full text |Cite
|
Sign up to set email alerts
|

A 1-4 year follow-up study of 306 cases of stroke.

Abstract: To study the long-term prognosis of stroke, we performed annual follow-up examinations on 306 patients who had survived cerebrovascular accidents. All patients had been admitted to the Neurology Service, First Teaching Hospital, Beijing Medical College from January 1, 1976, to December 31, 1978, and were followed up for 1 to 4 years. The series included 217 cases of cerebral thrombosis, 54 of cerebral hemorrhage, and 35 of TIA. The life-table method was used to determine the cumulative survival rate (CSR), cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…In keeping with previous studies, advanced age could lead to severe stroke and have a deleterious impact on its prognosis [12][13][14][15][16][17][18]. Notably, rare studies indicated initial pulse rate as an important mortality predictor for ischemic stroke.…”
Section: Mortality Predictors and Survivalsupporting
confidence: 78%
See 2 more Smart Citations
“…In keeping with previous studies, advanced age could lead to severe stroke and have a deleterious impact on its prognosis [12][13][14][15][16][17][18]. Notably, rare studies indicated initial pulse rate as an important mortality predictor for ischemic stroke.…”
Section: Mortality Predictors and Survivalsupporting
confidence: 78%
“…NIHSS score at admission have been determined as other predictive factors for severe stroke and death of ischemic stroke patients [13][14][15][16][17][18]. Therefore, it is obviously important to recognize the most considerable economic and mortality predictors of stroke.…”
Section: Journal Of Neurology and Neurophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…We retrieved 28 studies [15–42] of patients with ischaemic strokes. Except for four [17,21,25,34], all remaining studies have found that, irrespective of the subtype of the index stroke, the recurrence hazards were highest shortly after it had occurred, with about a quarter [32] to half [15] of the risk at 1 year being accrued during the first 30 days and with a decline in the recurrence hazards during the subsequent 2–5 years. The ratio between the observed rates of recurrent strokes and the expected age‐adjusted rates of a first ever stroke has been similarly reported to decline.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20][21][22]. Recurrence rates follow ing the initial hemorrhage are 3-7% at 1 year and 19% at 5 years [17][18][19]. The period with the highest risk of recurrence depends upon the type o f the first stroke.…”
mentioning
confidence: 99%